Implementation of a Project Management Office in a Public Sector Organization: A Case Study Involving a Sanitation Institution - Esquierro, José Carlos; Valle, André Bittencourt; Soares, Carlos Alberto Pereira; Vivas, Dácio Castro (International Review of Management and Marketing, 2013)
This paper proposes recommendations for improving the implementation of a Project Management Office (PMO) in a government organization. Such organizations can face uncertainties due to unpredicted and unexpected environmental events. The methodology used here was based on review of the literature, experience of the authors, and analysis of the process to be employed to create a PMO in the Department of Municipal Water and Sewage Systems (SEMAE), Brazil. This study aims to show how implementing a PMO can ensure proper management of strategic projects related to conservation of water resources. The PMO plays an important role in the implementation of strategic projects for public sanitation. This study also shows that the effectiveness of actions taken by the PMO is strongly influenced by how this process is implemented. Keywords: Project Management Office; Sanitation Institutions; Water JEL Classifications: M20